The Role of Employer Branding and Work Motivation to Create Employee Engagement at XYZ University - Parashakti, Ryani Dhyan; Windayanti, Windayanti; Aditya, Acep Tedi (Dinasti International Journal of Digital Business Management, 2024)
The strategic role of human resources can give an organisation strength in realising its business goals. One of the organisational strengths of human resource management is employee engagement. Gallup Organisation likens employee engagement as a positive emotional bond that employees have and the commitment that employees have (Gallup, 2013). The company must have a good strategy so that employees have a good commitment to the company and the intention to leave will be reduced. Employer Branding is a strategy or company to create a pleasant work environment, positive and competitive behaviour, good teamwork, a good reward system, good organisational governance, and a culture of learning and adequate training, with this, employees will be proud to work because the company is cared for, therefore employees will improve performance for the better and be comfortable at work so as to reduce the intensity of employees to leave the company voluntarily. XYZ University with new management and ownership changes has a management strategy that can realise employee attachment to the organisation. The organisation will get a lot of human resource strength in line with the strategy run by the organisation. This research uses qualitative methods with data collection techniques through interviews, observations, documentation studies. Data validity and data credibility were tested using triangulation techniques. The subjects of this study were five employees from the leadership level and non-academic staff. The result of this research is XYZ University implements employer branding by providing motivation to increase employee engagement.